2015
DOI: 10.3109/10428194.2014.979413
|View full text |Cite
|
Sign up to set email alerts
|

Primary diffuse large B-cell lymphomas of central nervous system exhibit remarkably high prevalence of oncogenic MYD88 and CD79B mutations

Abstract: MYD88 and CD79B mutations that activate nuclear factor (NF)-κB signaling are prevalent in subsets of diffuse large B-cell lymphoma (DLBCL). We examined the prevalence of somatic mutations in the Toll/interleukin-1 receptor (TIR) domain of MYD88 and the tyrosine-based activation motif (ITAM) domain of CD79A/B in 18 primary central nervous system (CNS) DLBCLs, and their immunoprofile. MYD88 mutation was found in 17 cases (94.4%), all of which were L265P substitutions. CD79B mutation was found in 11 cases (61.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 18 publications
9
55
0
Order By: Relevance
“…The frequent utilization of V H 4-34 in ABC DLBCL cases is consistent with previous work demonstrating an enrichment for V H 4-34 among DLBCL cases classified as "non-GCB" by immunostaining (20). Primary central nervous system lymphoma (PCNSL) is a type of DLBCL that has an ABC phenotype (38) and acquires several of the pathognomonic mutations of ABC DLBCL (39)(40)(41)(42). V H 4-34 is used in 55% of PCNSL cases, an enrichment that suggests that this V H segment confers a selective advantage in PCNSL, as in nodal ABC DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent utilization of V H 4-34 in ABC DLBCL cases is consistent with previous work demonstrating an enrichment for V H 4-34 among DLBCL cases classified as "non-GCB" by immunostaining (20). Primary central nervous system lymphoma (PCNSL) is a type of DLBCL that has an ABC phenotype (38) and acquires several of the pathognomonic mutations of ABC DLBCL (39)(40)(41)(42). V H 4-34 is used in 55% of PCNSL cases, an enrichment that suggests that this V H segment confers a selective advantage in PCNSL, as in nodal ABC DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that a high frequency (>75%) of MYD88 L265P mutations (an adaptor protein mediating toll-like receptor and interleukin-1 signaling) in the DLBCL subtype of PCNSL may be an initiator of disease. Additionally, most MYD88 L265P-positive patients have CD79B or CARD11 mutations (B cell receptor signaling pathway)282930. In addition, the constitutive activation of the nuclear factor (NF)- κB pathway is a hallmark of B cell PCNSL31.…”
Section: Discussionmentioning
confidence: 99%
“…2). MYD88 L265P mutations are also reported in a small proportion of other SBLs and a subset of large B cell lymphomas of non-germinal center/activated B cell type, particularly those of leg type and those at immune privileged sites (CNS and testis) [25, 36, 62]. The variable results for the reported frequency of MYD88 mutation in LPL and other lymphoid neoplasms relate in part to use of detection methods with different sensitivities, differences in the proportion of neoplastic cells in the samples studied, possible inclusion of misdiagnosed cases with a lack of tissue confirmation in some studies, and some results based on investigation of very few cases.…”
Section: Lymphoplasmacytic Lymphoma and The Impact Of Myd88 L265p Mutmentioning
confidence: 99%